Island of Thieves - Lacey, Josh (Houghton Mifflin, 2012)
Tom goes with his Uncle Harvey to Peru, where they narrowly escape imprisonment and death as they hunt for buried treasure after tracking down a journal written by John Drake, a young relative of Sir Francis Drake, on a voyage to Lima in 1577. Includes biographical information on John and Francis Drake.